2018
DOI: 10.3390/metabo8010017
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Serum Metabolomic Profile in Nonalcoholic Fatty Liver Disease: Research and Clinical Perspectives

Abstract: In recent years, metabolomics has attracted great scientific attention. The metabolomics methodology might permit a view into transitional phases between healthy liver and nonalcoholic steatohepatitis. Metabolomics can help to analyze the metabolic alterations that play a main role in the progression of nonalcoholic steatohepatitis. Lipid, glucose, amino acid, and bile acid metabolism should be widely studied to understand the complex pathogenesis of nonalcoholic steatohepatitis. The discovery of new biomarker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 48 publications
3
29
0
Order By: Relevance
“…On the HFD, XOS diminished the levels of cecal metabolites tyrosine and isovalerate, whose reduction likely contributed to the increased hepatic fat oxidation. We assume this because higher levels of tyrosine have been observed in NASH patients [ 48 ] and, in addition, dysregulated metabolism of tyrosine has been documented in them [ 49 ]. The consequences of the dysregulated metabolism of tyrosine are not entirely clear, but it has been proposed that tyrosine could enter the ketogenic pathway, in which it will be metabolized directly to acetyl-CoA [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the HFD, XOS diminished the levels of cecal metabolites tyrosine and isovalerate, whose reduction likely contributed to the increased hepatic fat oxidation. We assume this because higher levels of tyrosine have been observed in NASH patients [ 48 ] and, in addition, dysregulated metabolism of tyrosine has been documented in them [ 49 ]. The consequences of the dysregulated metabolism of tyrosine are not entirely clear, but it has been proposed that tyrosine could enter the ketogenic pathway, in which it will be metabolized directly to acetyl-CoA [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diet-induced liver disturbances often trigger alterations in glycolysis which can cause a rise in circulating pyruvate. 41 This may explain the elevated pyruvate levels in DKO sera. In DKO sera, our 1 H NMR analysis revealed that glycine levels were lower than that in ApoE KO sera which supports findings from other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Application of MaS allografts was increased over time-period ( Supplementary Figure S2 ). Amount of metabonomic analysis on serum, plasma, urine, liver tissue or even salivar samples from NAFLD/NASH patients in general population were performed to discriminate the suspicious objects, uncover the mechanism and evaluate the efficiency of medical treatment on hepatic steatosis ( Gitto et al, 2018 ; Troisi et al, 2019 ). However, less metabonomic analysis was performed on grafts discriminated by MaS status before.…”
Section: Discussionmentioning
confidence: 99%